Hypogonadism in chronic obstructive pulmonary disease (COPD) – risk factors - Novkovic, Ljiljana; Lazic, Zorica; Petrovic, Marina; Cupurdija, Vojislav; Vujanac, Katarina; Cekerevac, Ivan (Vojnosanitetski pregled, 2021)
Abstract Bacground/Aim. Chronic obstructive pulmonary disease (COPD) is the leading cause of morbidity and mortality in pulmonary pathology. However, apart from its own pulmonary manifestations, this disease is also characterized by systemic effects, including hypogonadism which is described especially in the group of men with COPD. The aim of this study was to evaluate risk factors for hypogonadism in men with COPD. Methods. The study included 96 male patients with COPD in stable phase of the disease. All patients were checked for concentration of free testosterone in serum, markers of systemic inflammation, tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and C reactive protein (CRP), pulmonary function test, gas exchange parameters, a 6-minute walk test (6MWT), nutritional status and condition of skeletal muscle (midthigh muscle cross-sectional area – MTCSA using computed tomography). Results. Decreased value of free testosterone was found in 37.5% of the patients. In the group with hypogonadism (free testosterone
Keywords: hypogonadism; pulmonary disease, chronic obstructive; risk factors